AESTHETIC CHINESE PAINTING TECHNIQUE BY ARTISTS LEE MAN FONG - Gani, Sangid Zaini (CAIJ: Creative Arts Interdisciplinary Journal, 2022)
Chinese painting is an artistic entity with its own rules and arguments that make its paintings unique and distinctive. This article is specifically about the Chinese painting of Lee Man Fong. His background is that of an artist living and working in the Chinese diaspora in Indonesia, who used to be a trusted assistant to President Sukarno in selecting artworks for the State Palace. This problem attempts to explain the aesthetic aspect of understanding traditional Chinese painting, which deviates from the principles of ancient Chinese painting. Applying a descriptive analysis method with an aesthetic approach aims to decipher the meaning contained in Lee Man Fong’s work, which shows a tendency toward Chinese painting, such as the presence of objects like birds, fish, and female figures against the background of elements of Taoist and Confucian beliefs in his works. unconsciously with the principles of the canon of Chinese art realised in the Xieyi style, one of the trends in Chinese painting. Keyword: Lee Man Fong, Xieyi, Chinese Painting